Conventional Full Denture Prosthodontics - Zicha, Antonín (Karolinum, 2024)
This textbook provides essential information about the principles and procedures involved in the fundamentals of conventional prosthetic rehabilitation. The textbook is organized into 16 chapters with illustrations and presents the following topics: principles of retention, basics of anatomy and physiology of the edentulous mouth, patient's examination, management and denture fabrication (divided into a clinical and a laboratory part), the immediate complete denture, rebasing and repairs of dentures. 80 illustrations included in the textbook help to improve the visualization for the readers. This textbook is recommended for all students of dental faculties of medical universities as well as for postgraduate dental students and dental technicians.
Keywords: Stomatologie